Ziswaf Role in the Formation of Justice of the Muslim Redistributive - Nurlailiyah Aidatus Sholihah; Fikry Ramadhan Suhendar (International Journal of Nusantara Islam, 2021)
Ownership in Islam is essentially belongs to God and man is merely a surrogate recipient of Him. Everything that God entrusted to man should be put to good use in order to create a justice that is the core of Maqasid ash-Shari'ah. To create the justice, Islam requires that every Muslim who is able to issue a charity. With the obligation to pay zakat is expected to reduce the inequities that exist in society. In the economic field, the Muslim economists have different models related to the role of zakat to achieve justice. This article aims to explain some of the models as expressed by Chapra, Choudury and other economists. The method used in this paper is a descriptive analytical method, where the authors will describe the models offered by economists for analysis to obtain the proper model as a solution if it can be applied in Indonesia. Data obtained by the literature search, which the authors seek the literature relating to the charity as well as the opinions of economists in overcoming injustice in society. According to Chapra there are four aspects to realize maqashid mutually reinforcing and can give effect to the allocation and distribution of existing resources. in which authors seek the literature relating to the charity as well as the opinions of economists in overcoming injustice in society. According to Chapra there are four aspects to realize maqashid mutually reinforcing and can give effect to the allocation and distribution of existing resources. in which authors seek the literature relating to the charity as well as the opinions of economists in overcoming injustice in society. According to Chapra there are four aspects to realize maqashid mutually reinforcing and can give effect to the allocation and distribution of existing resources.